Creative Problem Solving Model to Student’s Problem Solving Ability in Natural Science Learning for Primary Students - Sumiati Pulungan; Yanti Fitria (Budapest International Research and Critics University, 2021)
The purpose of this research is to find out out the effect creative problem solving model to student’s problem solving ability in natural science learning for primary students. the research used a quantitative approach with experimental research by using quasi-experiment. This research was done in SDN 060827 at grade V consisting of two paralel classes and the object of the research was 30 students with two paralel classes. The data collection techniques obtined by students’ sheet of learning activity and observation sheet for Assessment and interview. The research procedure was used planning, action, observation, and reflection. The result of this research were students’ ability to solve problem could improve by using the Creative Problem Solving (CPS) model in the classroom interaction of natural science learning for primary students.